Synthetic ligands of the elastin receptor induce elastogenesis in human dermal fibroblasts via activation of their IGF-1 receptors. Issue 3 (December 2015) - Qa'aty, Nour; Vincent, Matthew; Wang, Yanting; Wang, Andrew; Mitts, Thomas F.; Hinek, Aleksander
Highlights: Synthetic peptides with xGxxPG sequence induce elastogenesis in dermal fibroblasts. Similar sequence is also present in the IGF-1-binding protein-1. All these peptides interact with the elastin receptor, then cross-activate IGF-1R. Interaction between xGxxPG peptides and IGFBP-1 also releases free IGF-1. Free IGF-1 binds to its receptor, thereby activating elastogenic pathway. Abstract: Background: We have previously reported that a mixture of peptides obtained after chemical or enzymatic degradation of bovine elastin, induced new elastogenesis in human skin. Objective: Now, we investigated the elastogenic potential of synthetic peptides mimicking the elastin-derived, VGVAPG sequence, IGVAPG sequence that we found in the rice bran, and a similar peptide, VGVTAG that we identified in the IGF-1-binding protein-1 (IGFBP-1). Results: We now demonstrate that treatment with each of these xGVxxG peptides (recognizable by the anti-elastin antibody), up-regulated the levels of elastin-encoding mRNA, tropoelastin protein, and the deposition of new elastic fibers in cultures of human dermal fibroblasts and in cultured explants of human skin. Importantly, we found that such induction of new elastogenesis may involve two parallel signaling pathways triggered after activation of IGF-1 receptor. In the first one, the xGVxxG peptides interact with the cell surface elastin receptor, thereby causing the downstream activation of the c-Src kinase and a consequent cross-activation of the adjacent IGF-1R, even in the absence of its principal ligand. In the second pathway their hydrophobic association with the N-terminal domain (VGVTAG) of the serum-derived IGFBP-1 induces conformational changes of this IGF-1 chaperone allowing for the release of its cargo and a consequent ligand-specific phosphorylation of IGF-1R. Conclusion: We present a novel, clinically relevant mechanism in which products of partial degradation of dermal elastin may stimulate production of new elastic fibers by dermal fibroblasts. Our findings particularly encourage the use of biologically safe synthetic xGVxxG peptides for regeneration of the injured or aged human skin.